The Impact of Gut Microbiota on Chronic Obstructive Pulmonary Disease: A Dual-Sample Mendelian Randomization Study - Niu N; Zhao J; Li H; Miao Y; Chen F; Liu J; Cao L; Ji T; Gao F; Xie S; Zhang Y (International Journal of COPD)
Na Niu,1– 3,* Jian Zhao,4,* Haoxiang Li,1,3,* Yongen Miao,1,3,* Futao Chen,5 Junyong Liu,6 Limin Cao,5 Tuo Ji,7 Feng Gao,8 Shuanshuan Xie,1 Yunfeng Zhang9 1Department of Respiratory Medicine, Tenth People’s Hospital of Tongji University, Shanghai, People’s Republic of China; 2Department of Clinical Laboratory, Tenth People’s Hospital of Tongji University, Shanghai, People’s Republic of China; 3Tongji University School of Medicine, Shanghai, People’s Republic of China; 4Department of Emergency Department, Tenth People’s Hospital of Tongji University, Shanghai, People’s Republic of China; 5Department of Respiratory and Critical Care Medicine, The Second People’s Hospital of Lianyungang, Lianyungang, Jiangsu, People’s Republic of China; 6Department of Respiratory and Critical Care Medicine, Chenzhou No.1 People’s Hospital, Chenzhou, Hunan, People’s Republic of China; 7Department of Central Laboratory, The Second People’s Hospital of Lianyungang, Lianyungang, Jiangsu, People’s Republic of China; 8Department of Respiratory, Zhangjiagang Hospital Affiliated to Soochow University, Suzhou, Jiangsu, People’s Republic of China; 9Department of Pulmonary and Critical Care Medicine, Shanghai Putuo Liqun Hospital, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shuanshuan Xie, Email xieshuanshuan@aliyun.com Yunfeng Zhang, Email 1740487709@qq.comBackground: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of global mortality and disability. Previous research suggests a relationship between gut microbiota and COPD, yet the causal link remains unclear. Hence, we conducted a dual-sample Mendelian randomization study to elucidate the impact of gut microbiota on COPD.Methods: We utilized single-nucleotide polymorphisms (SNPs) as instrumental variables, and the Inverse Variance Weighted (IVW) method for primary analysis. We explored the causal linkage between gut microbiota species (Coprococcus2, Holdemanella, Allisonella, Anaerostipes, Lachnospiraceae UCG008, Lachnospiraceae UCG010, Prevotella9, Marvinbryantia, Ruminococcaceae UCG013) and COPD through the analysis of genome-wide association study (GWAS) data sourced from a Finnish database. Summary data for COPD (6,915 cases and 186,723 controls), Early onset COPD (3,508 cases and 212,197 controls), admission rate of COPD (9,113 cases and 212,292 controls), related infection of COPD (59,925 cases and 159,867 controls), respiratory dysfunction of COPD (1,031 cases and 186,723 controls), were from FinnGen consortium R7 GWAS.Result: Our analysis revealed statistically significant correlations between several genera and COPD. Coprococcus2 exhibits a consistent protective role throughout the progression of COPD, evident in both typical COPD [OR=0.750, 95% CI (0.601– 0.937)], early-onset cases [OR=0.686, 95% CI (0.511– 0.920)], COPD-related hospitalizations [OR=0.724, 95% CI (0.575– 0.910)] and infections [OR=0.301, 95% CI (0.094– 0.961)]. Holdemanella manifests as a consistent risk factor in the COPD incidence [OR=1.211, 95% CI (1.063– 1.380)], early-onset COPD [OR=1.214, 95% CI (1.019– 1.446)], COPD hospitalization [OR=1.225, 95% CI (1.072– 1.401)] and respiratory impairment (OR:1.645, 95% CI: 1.198– 2.258). Allisonella demonstrates protective attributes in COPD occurrence [OR=0.884, 95% CI (0.794– 0.984)]. Genera such as Anaerostipes, Lachnospiraceae UCG008, Lachnospiraceae UCG010, and Prevotella9 show protective effects specifically in early-onset COPD. Marvinbryantia and Ruminococcaceae UCG013 are consistently identified as risk factors in onset of typical COPD.Conclusion: Mendelian randomization studies confirm a causal link between gut microbiota and various COPD types and complications, offering new insights into the disease’s pathogenesis, prevention, and treatment.Keywords: gut microbiota, Mendelian randomization analysis, chronic obstructive pulmonary disease, gut–lung axis